Investigation of the impact of magnesium versus titanium implants on protein composition in osteoblast by label free quantification. Issue 6 (30th April 2020) - Omidi, M.; Ahmad Agha, N.; Müller, A.; Feyerabend, F.; Helmholz, H.; Willumeit-Römer, R.; Schlüter, H.; Luthringer-Feyerabend, B. J. C.
Abstract : To our knowledge, this is the first report describing and comparing the effects of magnesium and titanium biomaterials on human osteoblast proteome. Abstract : Metallic implant biomaterials predominate in orthopaedic surgery. Compared to titanium-based permanent implants, magnesium-based ones offer new possibilities as they possess mechanical properties closer to the ones of bones and they are biodegradable. Furthermore, magnesium is more and more considered to be "bioactive" i.e ., able to elicit a specific tissue response or to strengthen the intimate contact between the implant and the osseous tissue. Indeed, several studies demonstrated the overall beneficial effect of magnesium-based materials on bone tissue ( in vivo and in vitro ). Here, the direct effects of titanium and magnesium on osteoblasts were measured on proteomes levels in order to highlight metal-specific and relevant proteins. Out of 2100 identified proteins, only 10 and 81 differentially regulated proteins, compare to the control, were isolated for titanium and magnesium samples, respectively. Selected ones according to their relationship to bone tissue were further discussed. Most of them were involved in extracellular matrix maturation and remodelling (two having a negative effect on mineralisation). A fine-tuned balanced between osteoblast maturation, differentiation and viability was observed.